Peran “Sentra Satria” Baturraden Dalam Melaksanakan Rehabilitasi Sosial Terhadap Anak Penyalahguna Narkotika Sebagai Upaya Mencegah Residivis - Arrafi Agusti Satrio Wibowo; Ikama Dewi Setia Triana; Muhammad Yusril Irza (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2025)
Narcotics abuse among children is a social problem that is increasing and requires serious attention. This research aims to analyze the role of the Baturraden Satria Center in carrying out social rehabilitation for children who abuse narcotics as an effort to prevent recidivism. The research method used is empirical normative legal research with a qualitative descriptive approach. Data was obtained through interviews with expert sources and relevant literature studies. The research results show that the Baturraden Satria Center has various social rehabilitation programs, such as mental development, psychosocial support, as well as skills training programs for children who have undergone rehabilitation. However, there are still several obstacles in implementing the program, such as limited dormitories for beneficiaries. Therefore, it is necessary to increase cooperation between government, society and families in supporting the successful rehabilitation of children who abuse narcotics so that brands can return to functioning socially in society without repeating the same actions.